Physicians certified by the American Board of Obesity Medicine provide evidence‐based care. Issue 1 (10th September 2020) - Gudzune, Kimberly A.; Wickham, Edmond P.; Schmidt, Stacy L.; Stanford, Fatima Cody
Summary: Our objective was to determine the clinical services offered by American Board of Obesity Medicine (ABOM) Diplomates and whether guideline concordant services varied by clinical practice attributes. We conducted a cross‐sectional analysis of the 2019 ABOM Diplomate survey (response rate 19.2%). Respondents (n = 494) self‐reported services offered: nutrition, exercise, mental health, minimally invasive bariatric procedures, perioperative bariatric surgical care and FDA‐approved anti‐obesity medications. We graded concordance of services offered with three evidence‐based obesity guidelines, and then conducted bivariate analyses comparing concordance by practice attributes. Most responding ABOM Diplomates offered nutrition (90.1%), exercise (67.8%) and mental health (76.7%). Few offered minimally invasive procedures (24.3%), and most provided perioperative surgical care (63.0%). Most (83.4%) prescribed FDA‐approved medications—typically both short‐ and long‐term agents (70.9%). Few Diplomates had low concordance with the American Heart Association/American College of Cardiology/The Obesity Society (AHA/ACC/TOS) guidelines (24.7%). Those who managed more obesity‐related conditions and endorsed AHA/ACC/TOS guideline use had higher concordance with these recommendations. No differences in guideline concordance existed by population, clinical effort or location. We found similar findings regarding concordance with ) American Association of Clinical Endocrinologists/American College of Endocrinology and Obesity Medicine Association guidelines. In conclusion, most responding ABOM Diplomates offer evidence‐based obesity medicine services. Clinicians may therefore have increased confidence in patient receipt of evidence‐based care when referring to an ABOM Diplomate.